A new approach for efficient wind power generation through helix wind turbine - Ahmed, Shakil; Khan, Md. Shafi Monjur; Islam, Mohaimenul; Jannat, Rahtul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.